Development of an Antimicrobial Material Based on a Nanocomposite Cellulose Acetate Film for Active Food Packaging - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M; Torres-Mediano, A (Taylor and Francis Ltd., 2014)
Nanocomposites based on biopolymers have been recognised as potential materials for the development of new ecofriendly food packaging. In addition, if these materials incorporate active substances in their structure, the potential applications are much higher. Therefore, this work was oriented to develop nanocomposites with antimicrobial activity based on cellulose acetate (CA), a commercial organoclay Cloisite30B (C30B), thymol (T) as natural antimicrobial component and tri-ethyl citrate (TEC) as plasticiser. Nanocomposites were prepared by a solvent casting method and consisted of 5% (w/w) of C30B, 5% (w/w) of TEC and variable content of T (0%, 0.5% and 2% w/w). To evaluate the effect of C30B into the CA matrix, CA films without this organoclay but with T were also prepared. All nanocomposites showed the intercalation of CA into the organoclay structure; furthermore this intercalation was favoured when 2% (w/w) of T was added to the nanocomposite. In spite of the observed intercalation, the presence of C30B inside the CA matrices increased the opacity of the films significantly. On the other hand, T showed a plasticiser effect on the thermal properties of CA nanocomposites decreasing glass transition, melting temperature and melting enthalpy. The presence of T in CA nanocomposites also allowed the control de Listeria innocua growth when these materials were placed in contact with this Gram-positive bacterium. Interestingly, antimicrobial activity was increased with the presence of C30B. Finally, studies on T release showed that the clay structure inside the CA matrix did not affect its release rate; however, this nanofiller affected the partition coefficient KP/FS which was higher to CA nanocomposites films than in CA films without organoclay. The results obtained in the present study are really promising to be applied in the manufacture of food packaging materials. © 2014 Taylor & Francis.